ANALISIS PERSEDIAAN KEBUTUHAN GALANGAN (PLAT KAPAL) DENGAN METODE EOQ PADA PT PENGERUKAN INDONESIA - Vivian Karim Ladesi; Tasya Agustin; Winoto Hadi (LOGISTIK, 2021)
Inventory is one of the fundamental problems in a business. Without inventory, a business will be faced with a variety of problems, for example, not having the option to fulfill client orders that lead to loss of client trust, inhibiting interaction creation, etc. Therefore, this study will analyze the management of ship plate inventory at PT Pengerukan Indonesia. There is a technique used to control the supply of stock, namely the"Economic Order Quantity" (EOQ) method. The method used is quantitative by using two types of data, namely primary data and secondary data. The results of this study can produce efficiency of inventory costs where the total stock of uk plate 5mm company as much as 399 sheets and plate uk 12mm 419 sheets and companies make orders as much as 110 times a year. While using the EOQ method the company only orders the purchase of plates as many as 35 times a year with a 10-day message period with a total requirement when ordering as much as 11 pieces for uk 5mm and 12 sheets for uk 12mm and experience cost efficiency of Rp37,280,302. for uk 5mm plates and Rp37,673,245 for uk 12mm plates.